Extracellular Vesicles from Regenerating Skeletal Muscle Mitigate Muscle Atrophy in an Amyotrophic Lateral Sclerosis Mouse Model - Jinghui Gao; Aria Sikal; Rachel Hankin; Yaochao Zheng; Elijah Sterling; Kenny Chan; Yao Yao (Cells)
Amyotrophic lateral sclerosis (ALS) is a devastating neuromuscular disease characterized by progressive motor neuron degeneration and muscle atrophy, with no effective treatments available. Chronic inflammation, which impairs muscle regeneration and promotes proteolysis, is a key contributor to ALS-related muscle atrophy and a promising therapeutic target. Here, we applied extracellular vesicles (EVs) derived from regenerating skeletal muscles 14 days post-acute injury (CTXD14SkM-EVs), which possess a unique anti-inflammatory profile, to target muscle defects in ALS. We found that CTXD14SkM-EVs enhanced myoblast differentiation and fusion in a cellular muscle-wasting model induced by pro-inflammatory cytokine tumor necrosis factor alpha. Intramuscular administration of these EVs into an ALS mouse model mitigated muscle atrophy by promoting muscle regeneration, shifting macrophage polarization from pro-inflammatory M1 to anti-inflammatory M2 state, and suppressing the aberrant Nuclear Factor Kappa B (NF-κB) signaling, a key driver of muscle protein degradation. These results underscore the therapeutic potential of regenerating muscle-derived EVs for combating muscle atrophy in ALS.